Experimental investigation of free wing IIUM-UAV configuration - Omar, Ashraf Ali; Mohd Yusof, Mohammad Fairuzi; Mohd Sani, Mohd Afnan (2010)
In this work, the IIUM first free wing unmanned aerial vehicle model (IIUM-FWUAV) was investigated experimentally. The experimental work was carried out using IIUM low speed closed circuit wind tunnel. The aerodynamic performance of free wing concept was predicated. The effects of angle of attack and Reynolds number were also examined and discussed. In designing the experimental model the geometrical and kinematics similarity were considered. Foam, fiber glass, carbon fiber, wood, aluminum and steel are the main materials used to build the experimental model. The experimental data was presented in term of pressure coefficient distribution, flow visualization, lift and drag coefficient. Angle of attack ranged from -5° to 10° and Reynolds numbers ranged from 2.9498x105 to 4.95x105 were considered in the investigation. The experimental results showed that, for free wing UAV the distribution of pressure coefficients are behaves differently compared to the fixed wing UAV. The results also showed that the using of free wing configuration can delay or avoid the flow separation.